Subjective Age and Job Satisfaction: A Moderated Mediation Model of Job Burnout and Chronological Age - Muhammad Khalid Anser; Moazzam Ali; Farooq Anwar; Muhammad Usman (Frontiers Media S.A., 2020)
Corresponding to the growing calls for theory-driven research on the age-job satisfaction association, the present study investigated direct and indirect (via job burnout) relationships between subjective age (felt age) and job satisfaction. The study also examined the moderating role of chronological age on both direct and indirect (via job burnout) relationships between subjective age and job satisfaction. Survey data were collected in three waves (2 months apart) from 355 employees in 62 firms operating in various service and manufacturing industry sectors in Pakistan. Data were analyzed using structural equation modeling, PROCESS macro for SPSS, and bootstrapping technique. The results showed subjective age was negatively related to job satisfaction, both directly (β = −0.19, p < 0.001) and indirectly, via job burnout (β = −0.09, bootstrap 95% confidence interval limits did not overlap with zero; lower limit = −0.15, upper limit = −0.04). Interestingly, the interaction term (relative subjective age × chronological age) had a significant negative effect on the direct negative association between subjective age and job satisfaction (B = −0.12, p < 0.05) and a significant positive effect on the direct positive relationship between subjective age and job burnout (B = 0.14, p < 0.01), showing that chronological age moderated the direct relationships of subjective age with job satisfaction and job burnout, respectively. Importantly, the results showed that chronological age moderated the indirect association (via job burnout) between subjective age and job satisfaction [bootstrap estimate = −0.025, bias-corrected confidence interval (−0.06, −0.002)]. The present study contributed to the literature on the age-job satisfaction association by suggesting subjective age as an alternative vantage point to look at this link between age and job satisfaction. The findings carry useful practical implications that can help managers counter age stereotyping, employees' feelings of job burnout, and a low level of employees' job satisfaction.